1979
DOI: 10.1002/ijc.2910230304
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneously staining regions on marker chromosomes in malignancy

Abstract: Direct chromosome analysis with G-banding revealed homogeneously staining regions (HSR) in five of 16 human solid malignant tumours of different histological types. The HSR's were localized either terminally or interstitially on the marker chromosomes. The great stability of the HSR-carrying markers in the tumour cells suggests an interrelationship of malignant cell proliferation with the HSR. In a single case the HSR showed a moderate staining intensity for C-heterochromatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…A similar finding has been re ported for HSRs in a number of human tumors (Biedler and Spengler, 1976;B ai .aban-Mai.enbaum and G ilbert, 1977;K ovacs, 1979). Other HSRs, however, exhibit intermediate staining (Kovacs, 1979;M iller et al, 1979) or are intensely stained (B iedler and Spengler, 1976;B ostock et al, 1979) after C-banding. The reason for these differences should become clearer as more is learned about the DNA composition of the HSRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar finding has been re ported for HSRs in a number of human tumors (Biedler and Spengler, 1976;B ai .aban-Mai.enbaum and G ilbert, 1977;K ovacs, 1979). Other HSRs, however, exhibit intermediate staining (Kovacs, 1979;M iller et al, 1979) or are intensely stained (B iedler and Spengler, 1976;B ostock et al, 1979) after C-banding. The reason for these differences should become clearer as more is learned about the DNA composition of the HSRs.…”
Section: Discussionmentioning
confidence: 99%
“…The Johns Hopkins Medical School, 720 Rutland Avenue, Baltimore, MD 21205 (USA). and HSRs have been described in tumors of a number of species in a variety of cell types (for references, see L evan et al, 1977;Bar ker and Hsu, 1979; Kovacs, 1979), but they are rarely found together in the same cell.…”
mentioning
confidence: 99%
“…At the time of the DNA isolations, the mean (± SD) number ofdm per cell for the cell lines Y1-DM, Cl.2a, and Cl.3b was 69 + 57 (6-220), 32 ± 19 , and 27 ± 24 , respectively (range in parentheses). Therefore, despite the differences in the relative abundance ofpYdl-DISCUSSION HSRs and dm have been described in various tumor cell types of human and animal origin (19)(20)(21)(22). Evidence has been presented that these chromosomal anomalies result from a process of gene amplification (1,(3)(4)(5)22).…”
Section: Specific Association Of Amplified Sequences With Y1 Dmmentioning
confidence: 99%
“…Tumorigenesis is accompanied by a variety of molecular processes including DNA rearrangements (18, 21), oncogene activation (2) and amplification (5,24,25), and the appearance of double-minute chromosomes and homogeneously staining regions containing amplified DNA sequences (7,10,16).…”
mentioning
confidence: 99%